Comprehensive Analysis of Necroptosis in Pancreatic Cancer for Appealing its Implications in Prognosis, Immunotherapy, and Chemotherapy Responses - Fang, Kun; Tang, De-Sheng; Yan, Chang-Sheng; Ma, Jiamin; Cheng, Long; Li, Yilong; Wang, Gang (Frontiers in Pharmacology, 2022)
Objective: Necroptosis represents a new target for cancer immunotherapy and is considered a form of cell death that overcomes apoptosis resistance and enhances tumor immunogenicity. Herein, we aimed to determine necroptosis subtypes and investigate the roles of necroptosis in pancreatic cancer therapy. Methods: Based on the expression of prognostic necroptosis genes in pancreatic cancer samples from TCGA and ICGC cohorts, consensus clustering approach was implemented for robustly identifying necroptosis subtypes. Immunogenic features were evaluated according to immune cell infiltrations, immune checkpoints, HLA molecules and cancer immunity cycle. The sensitivity to chemotherapy agents was estimated with pRRophetic package. A necroptosis-relevant risk model was developed with multivariate cox regression analysis. Results: Five necroptosis subtypes were determined for pancreatic cancer (C1~C5) with diverse prognosis, immunogenic features and chemosensitivity. Especially, C4 and C5 presented favorable prognosis and weakened immunogenicity; C2 had high immunogenicity; C1 had undesirable prognosis and high genetic mutations. C5 was most sensitive to known chemotherapy agents (cisplatin, gemcitabine, docetaxel, and paclitaxel) while C4 displayed resistance to above agents. The necroptosis-relevant risk model could accurately predict prognosis, immunogenicity and chemosensitivity. Conclusion: Our findings provide a conceptual framework for comprehending necroptosis in pancreatic cancer biology. Future work is required for evaluating its relevance in the design of combined therapeutic regimens and guiding the best choice for immuno- and chemotherapy.